Effects of corn dried distillers grains with solubles or corn gluten feed on Boer-type growing goat diets - Elmenhorst, Kaysha L.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
There is lack of research on varying ingredients effect on goat growth performance. However, the number of goats in the U.S. has increased in the past 15 years from 1.3 to 2.6 million head (NASS, 2002 and 2017). This study aimed to help close that gap in knowledge by determining how replacing soybean meal (SBM) with corn gluten feed (CGF) or corn dried distillers grains with solubles (DDGS) would affect growth performance in Boer type goats. Seventy-five Boer type goats (29.6+ 0.2 kg, approximately 70 d of age) were used. Goats were assigned 1 of 5 treatments. Goats and treatments were randomly assigned to pen, with 3 goats per pen, and pen as the experimental unit. Treatments were isocaloric and isonitrogenous but varied in protein source: 1) SBM; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF. Goats, and feeders, were weighed weekly during the 35 d experiment. The GLIMMIX procedure of SAS was used to analyze the data, the accepted alpha was 0.05. No treatment differences were detected for final BW, ADG, G:F, or ADFI (P>0.05). By including corn products, DDGS or CGF, feed costs were lowered by approximately $0.04/kg of feed. Goats fed diets with DDGS and/ or CGF had lower (P=0.0008) feed cost/ goat than goats on the SBM diets. There was, however, no evidence (P>0.05) that the diets affected the feed cost/ kg of gain. In conclusion, the experiment supports that corn DDGS or CGF may be used as an economic replacement for SBM in Boer-type growing diets.
Keywords: Spring 2019